DO WE REALLY NEED LIVER TRANSPLANT SERVICE? FAMOUS LAST WORDS!! Need Liver Transplant Service? - Safdar, C. Aqeel (Pakistan Armed Forces Medical Journal, 2015)
"There is no reason anyone would want a computer in their home." -- Ken Olson, president, chairman and founder of Digital Equipment Corp., 1977.People in high places, have a penchant for making sweeping statements, similar to the statement given above. It seems laughable now, but may have been of some relevance according to the short term future assessment. But people of vision come up with dreams and ideas which turn out to be life-changing.Such examples are replete in history of medicine, and also in medical history of our country. Men of vision, like the Great Burki, in a single year decided to establish three institutions in our country which changed the way we practice medicine and postgraduate medical training. Some of these organizations may seem a bit wayward at the moment, but that is a problem of implementation and lethargy of the people at their helms of affair, not a lack of vision of its architect.Those who oppose change or innovation give anecdotal and dogmatic statements, usually not based on evidence or based on faulty evidence. Status quo has usually been the governing principle of many residents of high bureaucratic echelons."The abdomen, the chest, and the brain will forever be shut from the intrusion of the wise and humane surgeon." -- Sir John Eric Ericksen, British surgeon, appointed Surgeon-Extraordinary to Queen Victoria 1873.Famous last words! It is surprising that the above statement was made just fifty years before all these “forbidden” cavities were invaded by brave surgeons.It is not even forty years when heart surgery was contemplated in Pakistan Army Medical Corps by similar men of vision and vigor. Financial rationalization has always been the biggest argument… “we should be spending this money on clean water and sanitation!” or statements similar to these. True, these are the Principles of Health Economics. But my argument is: Are they mutually exclusive?Many ambitious projects were shot down because it was thought that this money should be diverted to some other on-going broad based projects; unfortunately, for one reason or another, the results of these mostly NGO advocated programs have not always been as tangible as expected, even after spending huge amounts of limited resources. The statistical gains expected are usually not what are projected by the “Planning Commissions”. Hence the forward looking, ambitious programs are deprived of support, without achieving the theoretical gains of many wide based, fluid programs. Investment into the future, or at least some part of investment should be in research and future training.These futuristic and apparently expensive and wasteful nurseries are where new generation of surgeons and scientists will be nurtured. Both have to start and persist side by side. Numbers are not always consistent with priceless gains in the shape of improving morale of the patients and their families… some things are not weighed in pennies and paisas!Historically a few of our early patients did not achieve the results expected when cardiac surgery or renal transplant or bone marrow transplants were started. But looking at the results now, most are spending useful productive lives; all because of timely investments in the shape of money and personnel in these newer and expensive institutes and treatments. Almost all have become or have the potential of being financially feasible and fully self sustainable.Many of these forward looking institutes have been the places where a whole new generation of world level doctors have trained and are training. Not only for our army, but our institutes have been the models and training institutes for upcoming similar centers all over the country.Liver transplant (LT) service is at the brink of making an entry in the services available to our army patients. Its rather belated start may have been due to some hesitation at all levels. Countries like India, China, Taiwan and South Korea which are at the forefront of Live Donor programs, took up the challenge. Many centers had set backs to begin with, but they learned from their mistakes and now receive patients from all over the world. Millions and millions of dollars are earned, and a significant number of those dollars came from patients in this country. We could have been there with them!But wisdom lies in not making the same mistakes.  A program, even if it is slow to start, having an institutional backing like that of our Army is bound to succeed. Hiccups and setbacks are part of any new program. Even the program by Starzl from his first attempt in 1963 did not really succeed till the 1980s[i]. India performed its first successful liver transplant in 1998, and Sanjay the biliary atresia patient is nearly 18 year old now[ii]. This was only after two unsuccessful attempts in 1995 and 1996[iii]. The last five years however, have seen a dramatic growth in LT in India, pediatric LT leading the initial way. The total number of pediatric liver transplants performed in India has now exceeded 350. More than 95% of these transplants are living related, another aspect which needs focused programs to enhance the deceased donor organs[iv].Pakistan has about 10 million people infected with hepatitis C, with high mortality and miserable ends[v]. Many may be eligible for and benefit from LT. Prevention of acquired causes which need LT and newer and promising medicines will always be there. But the current burden of disease in our country will need LT centers working full time for perhaps the next 100 years. Stenting and Statins have reduced the number of patients requiring CABG surgery, but the number of patients requiring surgery keeps on increasing. Again both treatments are not mutually exclusive. Both have to continue hand in hand.It is estimated that in the Pakistan Army personnel and their dependents the number of adults and children requiring urgent transplants in a year is about 160[vi]. The numbers are even higher in non army patients; many not even admitted or offered treatment in civil hospitals, sent home for tender, loving care! We have to come up to the needs and expectations of our patients. Almost all of them cannot even dream of seeking treatment abroad. Now is the time to start a program, which will eventually help spread such centers. Just look at the cardiology centers in the country, instigated in no small way by our own trailblazing Institute of Cardiology, which perhaps began at a time when resources were even less, but the spirit was higher."The Americans have need of the telephone, but we do not. We have plenty of messenger boys."- Sir William Preece, Chief Engineer of the British Post Office, 1876.Famous Last Words! We just cannot abandon our liver patients, of all ages, of all regions, having meager resources and many even unable to read or write. Just like the end stage heart diseases, renal failures, leukemias and sarcomas. Must give them a fighting chance at life!